Relationship between health literacy and prenatal care in young pregnant women - Hossien Izadirad; Shamsoddin Niknami; Iraj Zareban; Aliraza Hidarnia; Gholamreza Masoudy (Mashhad University of Medical Sciences, 2017)
Background and objective: Health literacy is as one of the determinant of social of  pregnant women's health. That affects the use of services and information of prenatal care. The aim of study was to determine the relationship between health literacy and prenatal care in young pregnant women. Methods:This descriptive- analytical study was carried out cross sectional in 2016. Research population, consisted of all Pregnant young women referring to urban health centers of Balochistan, 215 pregnant young women were selected according to a stratified sampling basis. Questionnaires Health Literacy for Iranian Adults (HELIA) and prenatal care was applied for data collection. Data were analyzed using descriptive statistics and Chi square test through SPSS19. Results: The mean age of pregnant women was 22.8 ± 7.79 years. The mean score of maternal health literacy was 67.69 ± 12.52 out of 100. 21.66% of studied women had insufficient health literacy, 26.04% not enough health literacy, 36.27% adequate health literacy and 15.81% high health literacy. There was a significant relationship between health literacy and taking iron tablet, multivitamin, and folic acid, diet, brushing and using dental floss (P˂0.05). Health literacy was not statistically significant with walking (P = 0.86). Conclusion: There is a significant relationship between maternal health literacy with prenatal care that shows the necessity of more attention to maternal health literacy in health promotion programs. Paper Type:Research Article.